Pengaruh Influencer Marketing dan Word Of Mouth terhadap Minat Beli Skincare Glad2Glow: Studi Kasus pada Mahasiswa Universitas Trunojoyo Madura - Hilya Sania Rosada; Mochammad Isa Anshori (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of influencer marketing and word-of-mouth on the interest of Trunojoyo Madura University students to buy Glad2Glow skin care products. Influencer marketing and word-of-mouth are seen as important factors in influencing consumer decisions when making purchases, especially in the beauty industry where recommendations and promotions play a big role. Using a questionnaire method, 22 students of Trunojoyo University Madura participated in this quantitative research. Data were analyzed using multiple linear regression techniques to determine the relationship between influencer marketing and word-of-mouth with purchase intention. The results showed that consumer intention to purchase Glad2Glow products is strongly and positively influenced by word-of- mouth and influencer marketing. These results provide insights to marketers on how to utilize customer recommendations and influencers to increase sales of skincare products in relevant target markets.